2022
DOI: 10.35848/1347-4065/ac42ae
|View full text |Cite
|
Sign up to set email alerts
|

Spurious-free thickness-shear bulk acoustic resonators on lithium niobate using standard and broadband piston mode designs

Abstract: This paper describes design and fabrication of sprious-free thickness shear bulk acoustic resonators (TSBARs) using the lithium niobate (LN) plate. Previously, the authors conjected from the experiment on the TSBAR that cutoff edges with crystal LN X-plane serve as ideal reflectors for the piston mode operation, and complete suppression is possible by adding the standard piston mode design to the other edges normal to the X-axis. Following to this conjecture, the traditional piston mode structure is designed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The authors showed that transverse modes experiencing propagation toward the crystal x direction can be suppressed by the use of free side boundaries (±x surfaces) in LN-based TSFBARs. 15,16,32) Thus, here we discuss only the plate wave propagation toward the y direction [see Fig. 1(a)].…”
Section: Transverse Modes Suppressionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors showed that transverse modes experiencing propagation toward the crystal x direction can be suppressed by the use of free side boundaries (±x surfaces) in LN-based TSFBARs. 15,16,32) Thus, here we discuss only the plate wave propagation toward the y direction [see Fig. 1(a)].…”
Section: Transverse Modes Suppressionmentioning
confidence: 99%
“…Thus, for the composition of LCRFs using an AlN-based BAW with a k 2 less than 7%, 12,13) coupler materials should possess extremely high or extremely low acoustic impedance Z a to make the coupling weak. [2][3][4][5][6] In contrast, LiNbO 3 (LN)-based thickness shear BAW resonators (TSBARs) [14][15][16] seem attractive for use in LCRFs because of an extremely large k 2 close to 40%, i.e. not so small Z a is required for the coupling layer.…”
Section: Introductionmentioning
confidence: 99%
“…The author's group reported 13) complete suppression of transverse mode resonances in TSBARs by applying the standard piston mode design to the Y side boundaries normal to the X-side boundaries in addition to the BPM to the X-side boundaries.…”
Section: Introductionmentioning
confidence: 99%